Workshop Penerapan Teknologi Qrcode pada Aplikasi Elivestock di Bumdes Panji Boma Ciamis - Irfan Darmawan; Alam Rahmatulloh; Rohmat Gunawan; Randi Rizal; Erna Haerani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
Goat farming in Indonesia, especially at the small and medium farmer level, is still largely carried out traditionally. Recording of livestock data related to pedigree, birth, weight and others, has not been done well by some farmers. Good livestock management is important because it has a direct impact on productivity, livestock health, cessation of livestock businesses and the welfare of farmers. Based on these problems, in this community service activity, training was carried out on the use of livestock recording applications (eLivestock) with the application of QRCode technology. There are three main activities carried out in this community service activity, including: preparation, implementation, evaluation and reporting. The community service activity was carried out on Monday, June 16, 2025, starting at 13:30 until finished, located at Panji Boma Farm, Werasari Village, Sadananya District, Ciamis Regency, West Java. After carrying out this community service activity, the partners were interested in using the application, and planned to make several preparations related to: information flow, data availability, report formats, software & hardware support and management officers.